Clinico-epidemiological profile of Acinetobacter and Pseudomonas infections, and their antibiotic resistant pattern in a tertiary care center, Western Nepal - Baral, Shankar; Pokharel, Anjila; Subramanya, Supram Hosuru; Nayak, Niranjan (Nepal Journal of Epidemiology, 2019)
Background: Infections caused by Acinetobacter species and Pseudomonas species, especially multidrug-resistant (MDR) strains pose a serious management challenge with a public health threat. Materials and Methods: A hospital-based retrospective study of patients who were infected with Acinetobacter spp or Pseudomonas aeruginosa was carried out at Manipal Teaching Hospital from 2014 to 2016. Results: A total of 170 cases of infections with Acinetobacter spp. and 313 cases with Pseudomonas aeruginosa were studied. The rate of nosocomial infections was higher than non-nosocomial infections. ICU was found as the major hub for both the organisms; (53.5% of cases due to Acinetobacter spp. and 39.6% due to Pseudomonas aeruginosa). Most isolates were of respiratory tract origin (Acinetobacter 74.7% and Pseudomonas aeruginosa 65.8%). Percentage resistance of Acinetobacter spp. towards polymyxin B was found to be quite low (18.8%). Similarly, resistance rates of Pseudomonas aeruginosa against amikacin were also found to be low, i.e., 17.4%. A higher prevalence of multidrug resistance was seen among Acinetobacter spp than among Pseudomonas aeruginosa (75.9% vs. 60.1%). The hospital stay was longer for patients infected with MDR isolate (p=0.001 for Acinetobacter spp. and p=0.003 for Pseudomonas aeruginosa). The mortality rate was higher in infections due to Acinetobacter spp (15.9%) as compared to Pseudomonas aeruginosa (8.3%). Conclusion: These clinico-epidemiological data will help to implement better infection control strategies. Developing a local antibiogram database will improve the knowledge of antimicrobial resistance patterns in our region, facilitating the treating physician in advocating empiric therapy if need be.